Guided Endodontics for Non-surgical Root Canal Retreatment: A Systematic Review - Samiei, Mohammad; Sabanik, Pouya; Tavakkoli Avval, Shiva (Iranian Endodontic Journal, 2025)
Introduction: This systematic review compared the accuracy of guided endodontics with the conventional method in non-surgical endodontic retreatment. Methods: Two reviewers conducted a systematic search across PubMed/MEDLINE, Scopus, Embase, and Web of Science databases. Inclusion criteria consisted of all in vitro studies up to October 2024 that documented the application of cone-beam computed tomography in creating a guide for endodontic retreatment cases. The reviewers assessed the quality of the selected studies using the QUIN tool. Data regarding the first author and publication year, sample size, tooth type, retreatment application, computer-aided navigation technique, groups, image acquisition method, outcome measures, guided technique results, conventional technique results, and the main results were extracted using a predefined template. Results: Based on our criteria, seven studies were included in this review. The studies demonstrated variability in the techniques utilized. Iatrogenic errors were less frequent in guided groups, regardless of the operator’s level of experience. Most studies indicated that guided endodontics was more effective than conventional methods, particularly in fiber post-removal and access through MTA, minimizing volumetric loss of tooth structure, and preserving fracture resistance. However, when using guided techniques for removal of separated instruments, more iatrogenic errors occurred, and more time was required compared to the freehand technique. Conclusion: Guided endodontics has shown promise in improving the outcomes of non-surgical retreatment by reducing complications. However, as all included studies were in vitro, clinical evidence is lacking, and the generalization of these results should be done cautiously. Further well-designed clinical studies are required to confirm these findings.